Reevaluating Nafkah Obligations: Female Muslim Scholars’ Insight and Ethics of Gendered Finance in Indonesian Families - Fadhilah, Nur; Hidayati, Nuril; Aisyah, Siti; Nurmahmudah, Nurmahmudah (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2025)
This study investigates how the Islamic legal obligation of nafkah, or spousal financial support, is reinterpreted in Muslim families in Indonesia through the lens of maqāṣid al-usrah. It aims to explore how gender dynamics, legal consciousness, and economic realities reshape the meaning and practice of nafkah beyond traditional legal prescriptions. Employing a qualitative socio-legal method, the research integrates doctrinal analysis with empirical insights drawn from in-depth interviews with seven female Muslim scholars from pesantren-based and higher education academic communities in East Java. Thematic analysis based on the principles of maqāṣid al-usrah reveals that while formal Islamic law defines nafkah as a unilateral male duty, lived experiences reflect a more collaborative and ethically responsive understanding. Informants demonstrate that financial responsibilities are frequently negotiated based on capability, mutual trust, and emotional stability, embodying values such as justice, compassion, and shared responsibility. The study further highlights how socio-cultural norms and internal religious reasoning influence women’s choices to either uphold or pragmatically reinterpret nafkah obligations. These findings underscore the relevance of maqāṣid-based approaches in bridging doctrinal ideals with everyday realities, offering a pathway for reforming Islamic family law toward greater gender equity and contextual sensitivity.